What Can a Catholic Learn from the History of Jewish Biblical Exegesis? - Anderson, Gary A (Studies in Christian-Jewish Relations, 2011)
This article considers the claim of the 2001 Pontifical Biblical Commission Study, The Jewish People and Their Sacred Scriptures in the Christian Bible that the Christian reader can be instructed by post-biblical Jewish reflections on the Bible. It explores Jewish understandings that the role of the biblical prophets was not only to communicate God's messages to Israel but also to represent Israel before God. The essay demonstrates the correctness of the PBC's assertion by applying this Jewish tradition about the prpohets to Christian reflection on the meaning of Jesus' death.